Applicability Analysis of HS Model in Large Diameter Monopile Foundation Engineering - PAN Bing; CHU Weijiang (Renmin Zhujiang)
The ultimate bearing capacity of the monopile foundation of an offshore wind turbine iscontrolled by the foundation deformation. It is very important to select the appropriate soilconstitutive model in the analysis and design of monopile foundation. Based on the results of thelateral loading tests of indoor pile foundation, this paper analyzes the applicability of variousmethods in the analysis of large diameter pile foundation engineering by comparing the lateralloading deformation characteristics of the pile foundation calculated by the three methods of HSmodel, MC model, and p-y curve, and their relationship with the test results. The research resultsshow that, within the ultimate lateral bearing capacity, both the p-y curve method and the MC modelwill overestimate the horizontal deformation resistance of the soil, and the calculation resultsof HS model are closer to the measured data, so it is more suitable for analysis and design oflarge diameter monopile foundation engineering.